Podcasting Pedagogies and the Sociocultural Dynamics of Flexible Learning: A Multidimensional Study of Gen Z Students in Urban Indonesia - Zuhriyah, Nabilaa Faizatuz; Ramadhan, Fatih Humam; Alifah, Nur; Lativah, Evi (Baileo: Jurnal Sosial Humaniora, 2025)
This study examines the multidimensional effectiveness of educational podcasts as alternative learning media among Generation Z university students in urban Indonesia. The research focuses on the perceptions, experiences, and preferences of digital-native learners toward flexible learning through narrative-based audio media. Using a qualitative case study approach, the research involved ten active students from various study programs in Jakarta who regularly accessed educational podcasts via Spotify for at least the past three months. Data were collected through semi-structured in-depth interviews, participant observation, and supporting questionnaires, and analyzed using thematic analysis. Findings reveal that podcast effectiveness is shaped by several key characteristics: storytelling-based narration, optimal duration (15–30 minutes), engaging communication style, and contextually relevant, applicable topics. The impact is multidimensional: cognitively, podcasts enhance comprehension and information retention; affectively, they foster learning motivation and emotional connection; behaviorally, they promote self-directed learning habits, informal discussions, and peer content-sharing. Listening habits integrated into daily routines—such as commuting, exercising, or bedtime—reflect a mobile and flexible learning habitus beyond the conventional classroom. This study expands the discourse in digital humanities and social sciences by framing podcasts not merely as learning tools but as cultural practices that signify a shift in how Gen Z students engage with knowledge. Audio-based pedagogy is recommended for integration into higher education curricula.